Age, intellectual functions and activity contributions to elderly nutritional status - Isnani Nurhayati; Anas Rahmad Hiadayat (International Journal of Public Health Science (IJPHS), 2020)
This research aimed to examine contribution of age, mental and activity to the status of elderly nutrition. The research conducted in Boyolali, Indonesia in December 2019-January 2020. This type of research is quantitative with a cross sectional approach; determination of sampling with purposive random sampling employed 70 respondents. Data analysis was using Path Analysis with linear regression rate of significance is 0.05.The results showed that contributions of the age, intellectual functions and simultaneous activities that directly affect the nutritional status of R2square=0.821 =0.674 or 67% while the remaining 33% are contributed from other variables. The amount of simultaneous age and intellectual functions contributions that directly affect elderly activities is R2square=0.0327 or 3.27%, the remaining 96.73% is influenced by other factors. Indirect contributions of age through activity to the status of elderly nutrition and there is direct contribution of elderly intellectual functions condition through activity to the status of elderly nutrition. <w:LsdException Locked="false" Priority="49" Na